Nutritional Status of Older Adults Who Are Overweight or Obese Compared to Those with a Healthy Weight, NHANES 2011–2014 (P01-001-19). (13th June 2019) - Jun, Shinyoung; Cowan, Alexandra; Bhadra, Anindya; Dodd, Kevin; Dwyer, Johanna; Eicher-Miller, Heather; Gahche, Jaime; Guenther, Patricia; Potischman, Nancy; Tooze, Janet; Bailey, Regan
Abstract: Objectives: The purpose was to evaluate nutritional status, food security, and related health factors of older adults who were overweight or obese compared to those with a healthy weight. Methods: Data from 2969 adults aged ≥60 years from NHANES 2011–2014 were analyzed. Participants were categorized by sex and body weight status as healthy weight (body mass index (BMI, kg/m 2 ) 18.5–24.9), overweight (BMI 25–29.9), or obese (BMI ≥ 30); underweight individuals were excluded. Healthy Eating Index (HEI)-2015 scores and total usual micronutrient intakes from foods and dietary supplements were estimated using two 24-hour dietary recalls and the National Cancer Institute method. Nutritional biomarkers, including serum vitamin D, vitamin B-12, and methylmalonic acid, and cardiometabolic risk factors were also assessed. Results: A substantial proportion of older adults (>30%) had intakes below Estimated Average Requirements (EAR) for calcium, magnesium, and vitamins C and D even with dietary supplements. Men and women with obesity had a higher prevalence of usual magnesium intakes <EAR compared to those with a healthy weight; among women only, the same was true for calcium, vitamins B-6 and D. Both men and women with obesity had significantly lower HEI-2015 scores than those with a healthy weight. The proportion of those with serum 25-hydroxyvitamin D < 40 nmol/L was higher in women with obesity (12%) than in women with a healthy weight (6%). Men and women who were overweight or obese were more likely to self-report fair/poor health, use ≥5 medications, and have cardiometabolic risk factors, including elevated blood pressure, triglycerides, and fasting blood glucose, and reduced high-density lipoprotein cholesterol, compared to individuals with a healthy weight. Women with obesity were more likely to be food-insecure and depressed, while men with obesity were less likely to consume government/community meals, compared to their counterparts. Conclusions: Older adults with obesity had higher risk of inadequate intakes for several key micronutrients, lower overall dietary quality, and higher prevalence of cardiometabolic risk factors compared to older adults with a healthy weight. Funding Sources: This work was supported by the National Institutes of Health.